Endoscopic Application of a Compact Compound-Eye Camera - Kagawa, Keiichiro; Kawahito, Shoji (Makara Journal of Technology, 2014)
A multi-functional compound-eye endoscope enabling multi-spectral imaging and variable field-of-view is presented, which is based on a compact compound-eye camera called TOMBO (thin observation module by bound optics). Narrow-band filters attached to some lenses provide snap-shot multi-band images. Fixed and movable mirrors are introduced to control the field of view, which realizes several observation modes such as three-dimensional shape measurement, wide field-of-view, and close-up observation.